2009
DOI: 10.1126/scisignal.2000431
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Phosphorylation Inhibits PKM2 to Promote the Warburg Effect and Tumor Growth

Abstract: The Warburg effect describes a pro-oncogenic metabolism switch such that cancer cells take up more glucose than normal tissue and favor incomplete oxidation of glucose even in the presence of oxygen. To better understand how tyrosine kinase signaling, which is commonly increased in tumors, regulates the Warburg effect, we performed phosphoproteomic studies. We found that oncogenic forms of fibroblast growth factor receptor type 1 inhibit the pyruvate kinase M2 (PKM2) isoform by direct phosphorylation of PKM2 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
714
5
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 673 publications
(758 citation statements)
references
References 24 publications
22
714
5
5
Order By: Relevance
“…So, inhibition of expression of PKM2 may also affect the proliferation of other cells. The superiority of PKM2 compared with PKM1 might be that it can balance energy supply and glycolytic phospho-metabolite pools by switching between two quaternary conformations (12)(13)(14)(15)(16)(17)(18). As is mentioned above, PKM2 can exist as an active tetrameric and an inactive dimeric form.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So, inhibition of expression of PKM2 may also affect the proliferation of other cells. The superiority of PKM2 compared with PKM1 might be that it can balance energy supply and glycolytic phospho-metabolite pools by switching between two quaternary conformations (12)(13)(14)(15)(16)(17)(18). As is mentioned above, PKM2 can exist as an active tetrameric and an inactive dimeric form.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that most PKM2 exists mainly as a dimeric form in tumor cells. Some viral oncoproteins like HPV-16E7 and pp60v-Src kinase (12,13) as well as cellular phosphotyrosine signaling (14,15) can induce the dimerization of PKM2, but the Ras oncogene induces the tetramerization of PKM2 (16,17). Recently, Kosugi et al (18) found that PKM2 activity is also regulated by direct binding of oncoprotein MUC1-C. Another important metabolic regulator of PKM2 is fructose 1,6-bisphosphate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…I Mor et al phosphorylation of tyrosine residues and proteinprotein interactions, are inhibitory (Hitosugi et al, 2009;Mazurek, 2011). The M2 isoform is expressed during embryonic development and is turned off in adult somatic cells (Hitosugi et al, 2009;Mazurek, 2011).…”
Section: Dapk Regulates Cell Metabolism Through Pkm2mentioning
confidence: 99%
“…The M2 isoform is expressed during embryonic development and is turned off in adult somatic cells (Hitosugi et al, 2009;Mazurek, 2011). A switch in the alternative splicing pattern leads to re-expression of the PKM2 during cancerous transformation and as a consequence, this isoform is almost ubiquitously expressed in tumors and proliferating cell lines (Clower et al, 2010;David et al, 2010).…”
Section: Dapk Regulates Cell Metabolism Through Pkm2mentioning
confidence: 99%